A BLAST AT THE PAST: AN INQUIRY INTO HERBERT SIMON'S ARGUMENTS AGAINST THE PRINCIPLES. (31st May 2013) - GEORGIOU, ION
<x xml:space="preserve">Abstract</x> The decades since 1946 have seen repeated rhetoric supportive of Herbert Simon's critique, published that year, of Luther Gulick's 'Notes on the Theory of Organization' (published in 1937). The literature offers few contrary opinions against this support. The present article presents a minute analysis of Simon's arguments against Gulick. The reason for this focus is that the rhetoric supportive of Simon's critique addresses the manner in which he argued against Gulick. It is shown how Simon's critique suffers from flawed and misleading argumentation, semantic incoherence, naïve simplicity, disproportionate emphasis, implied imputation, misdirected logic, historical misinterpretation, contextual overshooting, methodological incommensurability, false reproaches, misguiding charges, and an etiological approach unequipped to deal with complex webs of interrelationships.